2009
DOI: 10.1186/1471-2202-10-78
|View full text |Cite
|
Sign up to set email alerts
|

Estrous cycle influences the expression of neuronal nitric oxide synthase in the hypothalamus and limbic system of female mice

Abstract: Background: Nitric oxide plays an important role in the regulation of male and female sexual behavior in rodents, and the expression of the nitric oxide synthase (NOS) is influenced by testosterone in the male rat, and by estrogens in the female. We have here quantitatively investigated the distribution of nNOS immunoreactive (ir) neurons in the limbic hypothalamic region of intact female mice sacrificed during different phases of estrous cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 75 publications
7
33
1
Order By: Relevance
“…Intriguingly, in contrast with previous studies suggesting that estrogen could modulate hypothalamic nNOS gene expression [58,81,82,83,84], these changes in NO secretion seen during the estrous cycle are not associated with changes in nNOS protein synthesis but rather with changes in nNOS activity [62,85]. Estradiol induces the formation of a NMDA-R-nNOS complex in neurons of the preoptic region [62,85], thus enhancing NO secretion [86] by coupling nNOS to its main stimulatory calcium influx pathway [12,14] (box).…”
Section: Neuronal Nitric Oxide Modulates Gnrh Neuronal Activity and Scontrasting
confidence: 43%
“…Intriguingly, in contrast with previous studies suggesting that estrogen could modulate hypothalamic nNOS gene expression [58,81,82,83,84], these changes in NO secretion seen during the estrous cycle are not associated with changes in nNOS protein synthesis but rather with changes in nNOS activity [62,85]. Estradiol induces the formation of a NMDA-R-nNOS complex in neurons of the preoptic region [62,85], thus enhancing NO secretion [86] by coupling nNOS to its main stimulatory calcium influx pathway [12,14] (box).…”
Section: Neuronal Nitric Oxide Modulates Gnrh Neuronal Activity and Scontrasting
confidence: 43%
“…Increased numbers of nNitric oxide synthase immunoreactive neurons were found in the ARC during proestrus and in the POA during estrus. As these regions show large numbers of ERa, this study supports the conclusion of Pfaff and coworkers that E2 modulates expression of nNitric oxide synthase, which stimulates estrous behavior via activation of the nitric oxide signaling pathway (Sica et al, 2009). …”
Section: Genomic Regulation Of Estrous Behavior: Central Mechanisms Isupporting
confidence: 89%
“…Together, the products of these genes play a role in the induction of the behavioral expression of estrus. A recent study of Sica et al (2009) in female mice showed changes in nNitric oxide synthase expression in the hypothalamus during the estrous cycle. Increased numbers of nNitric oxide synthase immunoreactive neurons were found in the ARC during proestrus and in the POA during estrus.…”
Section: Genomic Regulation Of Estrous Behavior: Central Mechanisms Imentioning
confidence: 98%
“…There are many reports indicating that estrogen regulates nNOS expression in both up-and down-regulated manner. [37][38][39] Combined with the above discussion, sex hormone, especially estrogen, has a considerable impact on CA formation and can greatly influence CA formation. This is because there may be a different result in CA formation of eNOS-deficient mice with different sex.…”
Section: Discussionmentioning
confidence: 99%